Targeting the retinoic acid signaling pathway as a modern precision therapy against cancers - Lavudi, Kousalya; Nuguri, Shreya Madhav; Olverson, Zianne; Dhanabalan, Anantha Krishna; Patnaik, Srinivas; Kokkanti, Rekha Rani (Frontiers in Cell and Developmental Biology, 2023)
Retinoic acid (RA) is a vital metabolite derived from vitamin A. RA plays a prominent role during development, which helps in embryological advancement and cellular differentiation. Mechanistically, RA binds to its definite nuclear receptors including the retinoic acid receptor and retinoid X receptor, thus triggering gene transcription and further consequences in gene regulation. This functional heterodimer activation later results in gene activation/inactivation. Several reports have been published related to the detailed embryonic and developmental role of retinoic acids and as an anti-cancer drug for specific cancers, including acute promyelocytic leukemia, breast cancer, and prostate cancer. Nonetheless, the other side of all-trans retinoic acid (ATRA) has not been explored widely yet. In this review, we focused on the role of the RA pathway and its downstream gene activation in relation to cancer progression. Furthermore, we explored the ways of targeting the retinoic acid pathway by focusing on the dual role of aldehyde dehydrogenase (ALDH) family enzymes. Combination strategies by combining RA targets with ALDH-specific targets make the tumor cells sensitive to the treatment and improve the progression-free survival of the patients. In addition to the genomic effects of ATRA, we also highlighted the role of ATRA in non-canonical mechanisms as an immune checkpoint inhibitor, thus targeting the immune oncological perspective of cancer treatments in the current era. The role of ATRA in activating independent mechanisms is also explained in this review. This review also highlights the current clinical trials of ATRA in combination with other chemotherapeutic drugs and explains the future directional insights related to ATRA usage.